Effect of Concentration of NaOH and H2SO4 Catalysts on Hydrogen Gas Production Efficiency - Diah Iswandari; Idham Mahenri; Yohandri Bow; Adi Syakdani; Robert Junaidi (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
Indonesia has an ocean area of ​​5.8 million km2, water is the event of the decomposition of water compounds (H2O) into hydrogen gas (H2) and oxygen (O2) by using an electric current through water. In this study, the electrolysis of water at an electrolytic concentration containing NaCl can take place quickly with various catalysts of NaOH, and H2SO4 with concentrations of 0.1M, 0.25M, 0.5M, 0.75M, and currents of 15A, 25A and 35A. From the results of the study, it was found that the greater the current and the concentration of the catalyst, the greater the volume of gas produced and the efficiency of the flow, and a significant effect. The highest hydrogen gas produced was 0.4745 L at a concentration of 0.75M with a current of 35A for a NaOH catalyst and with a H2SO4 catalyst, gas with a volume of 0.48823L was produced at a current of 35A and a concentration of 0.75M and the highest current efficiency at a current of 35A the highest efficiency at a concentration of 0.75M was 89.354% for the NaOH catalyst, and the H2SO4 catalyst obtained the highest current efficiency at a concentration of 0.75M, which was 43.325%.